L1-norm minimization-based accurate diffraction field calculation method emitted by three-dimensional objects - ESMER, GÖKHAN BORA (SPIE-INT SOC OPTICAL ENGINEERING, 2018)
Accurate calculation of diffraction field emitted from a three-dimensional object paves the way to reconstruct more reliable information related to three-dimensional objects. As a result of this, we can analyze the structure of cells and perform precise measurements in non-destructive tests. Furthermore, accurate calculation of the diffraction field will help to improve the results in many applications of holography. In this work, we propose an accurate diffraction field calculation method which is based on L1-norm minimization and achieved successful results.
Keywords: Calculation Diffraction Field; Three-Dimensional Visualization; L-1-norm Minimization; L-2-norm Minimization